From a reader to a scientist: developing cirgi learning to empower scientific literacy and mastery of biology concept - Rizhal Hendi Ristanto; Siti Zubaidah; Mohamad Amin; Fatchur Rohman (Biosfer: Jurnal Pendidikan Biologi, 2018)
There are many studies on biology learning for primary school prospective teachers have been conducted in order to improve learning quality. This research aimed to produce a learning design in form of integrated instructional kit of CIRC and guided inquiry (CirGI). The research method used was research and development adapted from 4D development model of Thiagarajan consisted of define, design, develop, and disseminate stages. The research was limited up to the develop stage. The research result indicated that the product of CirGi instructional kit development in form of the syllabus, lesson plan, student worksheets, and evaluation instruments in form of scientific literacy and mastery of biology concept for primary school in Primary School Teacher Education in Pakuan University. The research result is expected to give a contribution to learning and to be further developed to achieve Biology learning objectives that could empower scientific literacy and the mastery of biology concept.